Kajian Ilmu-Ilmu Syari'ah Di Perguruan Tinggi : Sudahkah Merespon Tuntutan Masyarakat? - Mudzhar, M. Atho (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
This article is aimed at examining how the study of Shari'ah sciences in  the higher  learning  institutions  in Indonesia  has  been  conceptually  developed  over  time,  and assessing whether or not such a development has responded to meet the dynamic demand of modern Muslim communities in the world. To achieve the objective, the article started with the examination  of  the  epistemological  concepts  that  have  been used so far to maintain certain departments of studies or create new  ones  by  employing  a  three-layer  concept  of  Islamic  law studies (philosophical, normative, and empirical). Further, the article  undertook  a  comparative  analysis  of  how  the  study  of the  Shari'ah  sciences  had  been  developed  in  three  most relevant  countries  to  Indonesia,  namely  Egypt,  Saudi  Arabia, and  Malaysia,  where  the  creation  of  new  departments  in  the Faculty  of  Shari'ah  had  been  responsive  to  their  respective local demands. The article concluded that the study of Shariah sciences  in  Indonesia  had  been characterized  by  the  lack  of attention to studies of Usul al-Fiqh as indicated by the absence of  the department of  Usul al-Fiqh at either undergraduate or graduate  studies,  and  the  lack  of  advanture  to  integrate  the study of Shari'ah sciences proper with such modern demands  -apart from Islamic economics  - as in the field of human rights, taxation, industrial law, land reform, etc